High frequencies of F1534C and V1016I kdr mutations and association with pyrethroid resistance in Aedes aegypti from Somgandé (Ouagadougou), Burkina Faso - Sombié, Aboubacar (Trop Med Health, 2019)
BACKGROUND: Resistance to pyrethroid insecticides involving kdr mutations is widespread in Aedes aegypti (L.) (Diptera: Culicidae) and potentially could impact control efforts in endemic countries. Dengue cases had been sporadic in Burkina Faso for over a decade prior to the 2016–2017 outbreak that resulted in 15,074 suspected cases and 36 deaths, mainly in Ouagadougou. These outbreaks highlighted the lack of information on numerous aspects of the biology, behaviour and insecticide status of local dengue vector populations that are fundamental to vector control. RESULTS: We investigated the insecticide resistance profiles and the kdr mutations involved in pyrethroid resistance of Ae. aegypti from Somgandé, a district of Ouagadougou. WHO bioassays revealed that the local Ae. aegypti populations were highly resistant to pyrethroids with mortalities of 15% for permethrin and 37% for deltamethrin. Resistance to carbamates was also detected with mortalities of 55% for propoxur and 90% for bendiocarb, but high mortalities (> 97%) to organophosphates (malathion and fenitrothion) indicated susceptibility. Allele-specific PCR and voltage-gated sodium channel gene sequencing showed a very high frequency (97%) of the F1534C kdr allele whilst the V1016I kdr mutation frequency was 46%. Association of dual-locus kdr mutations was detected for permethrin resistance. CONCLUSION: We conclude that in this locality of Burkina Faso, Ae. aegypti is resistant to pyrethroid and carbamate insecticides but remains susceptible to organophosphates, providing useful information for possible future control.